Determinants of village apparatus performance, a comprehensive analysis of leadership style and work discipline - Deasy Rinayanti Pelealu (Jurnal Mantik, 2024)
This study investigates the determinants of Village Apparatus Performance through a multi-faceted analysis, incorporating measures of Leadership Style and Work Discipline. The examination begins with a rigorous assessment of the validity and reliability of the measurement instruments using the One-Sample Kolmogorov-Smirnov Test and Multicollinearity Test. Subsequently, a linear regression analysis is conducted to elucidate the individual and combined impacts of Leadership Style and Work Discipline on Village Apparatus Performance. The results indicate that while Leadership Style does not exhibit a statistically significant impact, Work Discipline emerges as a crucial determinant, with a highly significant influence on performance outcomes. Moreover, the combined effect of Leadership Style and Work Discipline demonstrates a synergistic impact, highlighting the interplay of these variables in shaping Village Apparatus Performance. The hypothesis testing further corroborates these findings, providing nuanced insights into the intricate dynamics of organizational performance within the village apparatus. These results carry practical implications for organizational strategies, emphasizing the imperative of fostering a disciplined work culture to enhance overall performance.